2011 16th International Solid-State Sensors, Actuators and Microsystems Conference 2011
DOI: 10.1109/transducers.2011.5969829
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of inductive proximity sensor using nanoporous anodic aluminum oxide layer

Abstract: This study presents an inductive proximity sensor implemented through the integration of nano-texture metal-spiral and np-AAO (anodic aluminum oxide (AAO) with nanopores) insulation layer on Si-substrate. The advantages of such nano-structure inductive proximity sensor are as follows, (1) The surface area of nano-texture metal-spiral is increased. Thus, the performance of inductive sensor is increased; and (2) The nano-texture metal-spiral consists of nanopores transferred from the AAO template. Thus, the eddy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…It was concluded that AAO/Al structure could be used to fabricate metal oxide gas sensors successfully. Lo et al [125] used anodic aluminum oxide with nanopores of about 50-60 nm to implement inductive proximity sensors. The anodic aluminum oxide was used as a template for patterning spiral film of gold.…”
Section: Aao Membrane In Sensors 331 Applications Of Aao Membrane In ...mentioning
confidence: 99%
“…It was concluded that AAO/Al structure could be used to fabricate metal oxide gas sensors successfully. Lo et al [125] used anodic aluminum oxide with nanopores of about 50-60 nm to implement inductive proximity sensors. The anodic aluminum oxide was used as a template for patterning spiral film of gold.…”
Section: Aao Membrane In Sensors 331 Applications Of Aao Membrane In ...mentioning
confidence: 99%
“…For instance, capacitive sensors have been used in positioning [15], [16]; humidity sensing [17], [18]; tilt sensing [19], [20]; pressure sensing [21]; and MEMS-based sensing [21]. Capacitors have also been applied as proximity sensors with applications to robotics, industrial monitoring and healthcare applications [22], [23], [24]. Products like Microchip's GestIC [25] have been introduced which allow for 3D gesture tracking using capacitive sensing using a rigidly-defined array shape.…”
Section: Related Workmentioning
confidence: 99%
“…For instance, capacitive sensors have been used in positioning [13], humidity sensing [14], tilt sensing [15], pressure sensing [16], and MEMS-based sensing [16]. The proximity sensor is a critical device with applications to robotics, industrial monitoring, mobile phone touch screens and healthcare [17], [18]. Our approach extends this body of work in two ways.…”
Section: Related Workmentioning
confidence: 99%